New concepts in the management of CAP: a focus on severe illness - MRSA and MDR pathogens - Niederman, Michael S. (Henry Stewart Talks, 2022)
Community-acquired MRSA, CA-MRSA pneumonia therapy, Serum procalcitonin, Steroids in severe CAP and COVID-19, Multidrug resistant pathogens